N-doped TiO2 nanoparticle based visible light photocatalyst by modified peroxide sol-gel method - Jagadale, Tushar C.; Takale, Shrikant P.; Sonawane, Ravindra S.; Joshi, Hrushikesh M.; Patil, Shankar I.; Kale, Bharat B.; Ogale, Satishchandra B. (Journal of Physical Chemistry C, 2008)
The peroxide gel route is employed to synthesize N-doped TiO2 nanoparticles (NP) at low temperature using titanium tetraisopropoxide, ethylmethylamine, and hydrogen peroxide as precursors. Structural studies show anatase phase in the undoped titania NPs as well as at 5 at. % N-doped titania NPs, although with a degree of matrix disorder in the latter case. The annealing of N-doped titania NPs at different temperatures shows that above 400 degrees C nitrogen escapes the O-Ti-O matrix and at 500 degrees C the sample becomes crystalline. Transmission electron microscopy reveals that the particle size is in the range of 20-30 nm for the undoped TiO2 but only 5-10 nm for N-doped TiO2. At higher nitrogen concentration (10 at. %) bubble-like agglomerates form. FTIR and photoluminescence quenching also confirm the incorporation of nitrogen in anatase TiO2. Optical properties reveal an extended tailing of the absorption edge toward the visible region upon nitrogen doping. X-ray photoelectron spectroscopy is used to examine the electronic state of doped nitrogen and the associated possible electronic modification of the TiO2 matrix. Under visible light irradiation the undoped TiO2 NPs do not show any significant photocatalytic activity, as expected; however, the 5 at. % N-doped TiO2 NPs show excellent activity.

Nano-heteroarchitectures of two-dimensional MoS 2 @ one-dimensional brookite TiO 2 nanorods: prominent electron emitters for displays - Devan, Rupesh S.; Thakare, Vishal P.; Antad, Vivek V.; Chikate, Parameshwar R.; Khare, Ruchita T.; More, Mahendra; Dhayal, Rajendra S.; Patil, Shankar I.; Ma, Yuan-Ron; Schmidt-Mende, Lukas (ACS Omega, 2017)
We report comparative field electron emission (FE) studies on a large-area array of two-dimensional MoS2-coated @ one-dimensional (1D) brookite (β) TiO2 nanorods synthesized on Si substrate utilizing hot-filament metal vapor deposition technique and pulsed laser deposition method, independently. The 10 nm wide and 760 nm long 1D β-TiO2 nanorods were coated with MoS2 layers of thickness ∼4 (±2), 20 (±3), and 40 (±3) nm. The turn-on field (Eon) of 2.5 V/μm required to a draw current density of 10 μA/cm² observed for MoS2-coated 1D β-TiO2 nanorods emitters is significantly lower than that of doped/undoped 1D TiO2 nanostructures, pristine MoS2 sheets, MoS2@SnO2, and TiO2@MoS2 heterostructure-based field emitters. The orthodoxy test confirms the viability of the field emission measurements, specifically field enhancement factor (βFE) of the MoS2@TiO2/Si emitters. The enhanced FE behavior of the MoS2@TiO2/Si emitter can be attributed to the modulation of the electronic properties due to heterostructure and interface effects, in addition to the high aspect ratio of the vertically aligned TiO2 nanorods. Furthermore, these MoS2@TiO2/Si emitters exhibit better emission stability. The results obtained herein suggest that the heteroarchitecture of MoS2@β-TiO2 nanorods holds the potential for their applications in FE-based nanoelectronic devices such as displays and electron sources. Moreover, the strategy employed here to enhance the FE behavior via rational design of heteroarchitecture structure can be further extended to improve other functionalities of various nanomaterials.